Civil Disobedience and Cyber Democracy - Mohd. Zain, Zawiyah (Richtmann Publishing Ltd, 2017)
The purpose of this paper is to analyze the emergence of civil disobedience in Malaysia specifically in the era of Abdullah Badawi, and its impact upon the democratization process. The whole analysis in this paper is qualitative and derived from two types of data which is primary and secondary data. The analysis shows that civil disobedience arose due to three factors, namely the government's failure to fulfill its promise to reform, Mahathir’s criticism against Abdullah Badawi's leadership, and the government failure to handle racial issues. Consequently, Barisan Nasional (The National Front) government failed to gain two-thirds majority of the parliamentary seats in the 2008 general elections and at the same time lost five states to the opposition. In 2013 general election the result remain the same which is government failed to gain two-thirds majority of the parliamentary seats. Furthermore, even though the emergence of civil disobedience failed to create a change of government, it however has been able to give birth to cyber democracy and create awareness among Malaysians to pursue the process of democratization